Suffering in the Workplace from a Philosophical View - Liberal Ormaechea, Sheila; Gismera, Eduardo; Paredes, Cristina; Sastre, Francisco Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Individual, family, economic, and other forms of people suffering impact organizations. Suffering in the workplace is probably a more common occurrence than expected in everyday life, and opposite to health and employee wellbeing. According to the World Health Organization, 300 million people worldwide struggle with depression and close to 800.000 people die due to suicide every year. The European Survey on Working Conditions in the European Union gathers the most varied aspects of working conditions, such as the duration of the working day, relationships between collaborators in organizations, or healthy work habits. Among the results of that survey it is noteworthy that almost half of the close to twenty-two thousand workers surveyed in the 27 member countries stated that they felt uneasiness due to the conditions of their work.